1973
DOI: 10.1073/pnas.70.5.1321
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Biphenyls: A New Type of Inducer of Cytochrome P-448 in the Liver

Abstract: The CO-difference spectrum of microsomes from rats treated with the polychlorinated biphenyls mixture, Aroclor 1254, has an absorption maximum at 448 nm. With ethylisocyananide as the ligand for reduced microsomes, Aroclor 1254 treatment causes a shift in the 455-nm peak to 453 nm and increases the ratio of absorbance of 455 nm to that at 430 nm from 0.53, obtained with untreated rats, to 1.24. These findings are similar to those seen in rats treated with the polycyclic hydrocarbon, 3-methylcholanthrene, but d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(47 citation statements)
references
References 27 publications
5
42
0
Order By: Relevance
“…4-CB induces cytochrome P-448-dependent enzymes and 6-CB induces P-450-dependent pathways in livers of offspring exposed to these congeners transplacentally and during lactation. Thus, the perinatal and adult livers respond to PCBs in much the same way (64)(65)(66). Our studies demonstrate that in developing rats, like adults, individual congeners are P-450 or P-448 inducers and that neonates may be more sensitive to PCBmediated increases in enzyme activities than adults.…”
Section: Modifications Of Ontogenymentioning
confidence: 99%
“…4-CB induces cytochrome P-448-dependent enzymes and 6-CB induces P-450-dependent pathways in livers of offspring exposed to these congeners transplacentally and during lactation. Thus, the perinatal and adult livers respond to PCBs in much the same way (64)(65)(66). Our studies demonstrate that in developing rats, like adults, individual congeners are P-450 or P-448 inducers and that neonates may be more sensitive to PCBmediated increases in enzyme activities than adults.…”
Section: Modifications Of Ontogenymentioning
confidence: 99%
“…Experiments aiming at assessing the inducibility of Cr(VI) reduction by PAM preparations showed that the PCB Aroclor 1254, which is a potent and wide-spectrum inducer of both microsomal (35) and cytosolic (7) enzymes, stimulated in rats a slight yet significant increase in activity.…”
Section: Discussionmentioning
confidence: 99%
“…properties of both the PB-and 3-MC-classes of inducers (Alvares ~ al., 1973;Vainio, 1974). Commerc ial preparations with higher degrees of chlorination have been found to be more potent inducers of monooxygenase activity than those of lower chlorination (Bickers et ~., 1972;Chen and DuBois, 1973).…”
Section: --mentioning
confidence: 99%
“…Polychlorinated biphenyls (PCBs) are industrial chemicals that are ubiquitous and persistent environmental contaminants, and are also potent inducers of xenobiotic monooxygenase activity (Risebrough et al, 1968;Nisbet and Sarofim, 1972;Wassermann et ~., 1979;Alvares et ~., 1973). Commercial PCB mixtures are complex assemblages of chlorinated bipheny 1 congeners which act as "mixed inducers" in rats, having…”
Section: --mentioning
confidence: 99%